Postural sway and breathing pattern among Malaysian recurve archers / Muhamad Noor Mohamed - Mohamed, Muhamad Noor (2013)
Postural movements and breathing pattern inconsistency potentially affect aiming stability in archery, thus contributing to challenges towards aiming task. Present study investigates postural sway and breathing pattern as factors that differentiate between skill level and whether these factors contribute to shooting performance. Forty-two recurve archers participated and were assigned into two groups, skilled (n = 21) and unskilled (n = 21), where their performance level was based upon rank tournaments (International Archery Federation [FITA]) score. For skilled group, it comprised of archers who had obtained scores of 1150 upon 1440. Unskilled group were archers who had never participated in any ranked tournaments but possessed the basic shooting knowledge. Their aged ranged 13 to 25 years old. Postural sway and breathing pattern were assessed by using Zephyr Bio-Harness at three phases; (i) set up, (ii) aiming, and (iii) release. Participants shot 12 arrows to a 30-meter target. Significant changes in postural sway across shooting phases were found only in skilled group (p < 0.05), while significant change in breathing pattern were noted for both groups (p < 0.05). Between group’s analyses, significance difference in postural sway were demonstrated for all phases (p < 0.05). Breathing pattern were found to be significant only during set up and aiming phase (p < 0.05). Postural sway during set up and release phase respectively (r = -0.168, p < 0.05 [set up], r = 0.278, p < 0.05 [release]) and breathing pattern during release phase (r = 0.129, p < 0.05) contributed to the shooting performance of skilled archers. Postural sway during set up phase (r = -0.108, p < 0.05) was the only contributor in unskilled archers shooting performance. Breathing pattern was found to affect postural sway in skilled group performances (r = 0.146, p < 0.05). Control of postural stability was proven to be difficult where most of the time athletes swayed due to automaticity of movements, division of attentional demands, technical flaws, and control of breathing pattern. The swayed was greater in unskilled archers. In summary, postural sway and breathing pattern contributed towards the shooting performance and the ability to cope with it guaranteed the accomplishment of the sport.